Fossil - Taylor, Paul D. (New York : Knopf, 1990)
A photo essay about different types of fossils, from bacteria and algae to birds and mammals.
Fossils-true and false -- Making of rocks -- Turning to stone -- Changing world -- Early paleontology -- fossil folklore -- Fossils of the future -- Remarkable remains -- Corals -- Sea bed dwellers -- Shells of all shapes -- Intelligent mollusks -- Animals in armor -- Arms and spines -- Fishes -- Plants-the pioneers -- Fossil fuels -- Out of the water -- Onto the land -- Sea dragons -- Fossil giants -- Discovering dinosaurs -- Discovering dinosaurs -- Winged wonders -- Mammal variety -- World apart -- Human fossils -- Living fossils -- Fossil hunting -- Index.
Keywords: Paleontology -- Juvenile literature; Fossils; Paleontology; Fossils; Paleontology-Juvenile literature